"We've Lost the Basics": Perceptions of Journalism Education From Veterans in the Field. (December 2018) - Ferrucci, Patrick
This study examines the perceptions that veteran digital journalists working at news organizations, the people who traditionally have hiring power, hold concerning how new entrants into the news industry are being prepared by journalism programs. Using in-depth interviews with 29 full-time digital journalists (journalists who only publish online), this study finds that while veterans said educators are doing a good job teaching technology, there is too much focus on it to the detriment of traditional journalism skills. These findings are then discussed through the lens of the theory of disruptive innovation.